Assessment of natural vegetation cover at the vicinity of Makkah city, Saudi Arabia - Abdulshakour, Jumana (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2024)
Makkah - Saudi Arabia, is one of the most important cities, which faced a reduction in natural vegetative cover, due to the hot aridity, with a maximum temperature around 40-49C, and scarcity of rainfall, the rate of rainfall is between 50-80 mm/year. A plant is supposed to be native if it has occurred naturally in a particular region, ecosystem, or habitat without human intervention. The aim of this study was to study the flora around Makkah city by choosing eight stands from different localities. The field work included relevé, the plots were about 10 × 10 meters in size. The study revealed that the eight stands were represented by 20 species belong to 8 families, Fabaceae and Apocynaceae were dominant by (34%), (25%) followed by Amaranthaceae (13%), Poaceae (12%) and Cucurbitaceae (5%); then (Apiaceae & Asteraceae) were represented by (4%), while Solanaceae was represented by only (3%) of the vegetation. Phanerophytes (40%) were the dominant while Hemicryptophytes (He) were the lowest value of life form (10%). The Floristic categories Saharo-Arabian (SA) and Sudano-Zambezian (AZ) were the dominant (38%), while Mediterranean (ME), Saharo-Sindian (SSI), Tropical (TR), Irano-Turanian (IT) were lowest value (6%). Rhazya stricta has a high number of species that were observed in native plants in study area (17%), while Cenchrus biflorus, Leptadenia pyrotechnica, Lycium shawii, Panicum turgidum, Senegalia asak, Senna italica, Stipellula capensis, Vachellia flava and Vachellia tortilis were the lowest with 3% over the stands. Finally, the diversity in species deficiency in Makkah.